Caracterização e localização de uma ATP-difosfoidrolase (Apirase, EC 3.6.1.5) em sarcolema cardíaco de ratos adultos - Oliveira, Edilamar Menezes de (1994)
In the present report we demonstrate an ATP-diphospho hydrolase (Apyrase, EC 3.6.1.5) in rat cardiac sarcolemma. The enzyme hydrolyses almost equally well different nucleoside di- and triphosphates. The calcium dependence and pH requirement were the same for the hydrolysis of ATP and ADP and the apparent Km values are similar for both Ca2+-ATP and Ca2+-ADP as substrates. Ca2+-ATP and Ca2+-ADP hydrolysis could not be attributed to the combined action of different enzymes because adenylate kinase, inorganic pyrophosphatase and nonspecific phosphatases were not detected in our assay conditions. The Ca2+-ATPase and Ca2+-ADPase activities were not affected by classical inhibitors of ATPase, adenylate kinase and alkaline phosphatase, thus excluding these enzymes as contaminants. Electron microscopic analysis revealed the presence of sealed vesicles indicating that the enzyme is plasma membrane-bound. The results demonstrate that an ATP-diphosphohydrolase is involved in the hydrolysis of ATP and ADP to AMP by the sarcolemmal membrane. The physiological role of this cardiac enzyme is unknown, but possibly it participate in the regulation of the cellular homeostasis.